High-sensitivity piezoceramic elements for medical ultrasonic examination equipment - Spiridonov, N.A.; Gusakova, L.G.; Pogybko, V.M.; Spiridonov, V.N.; Ischuk, V.M. (Functional Materials, 2008)
Results of investigation for production of piezoelectric ceramic elements (PCE) with high values of piezosensitivity g₃₃ are discussed. Industrial materials ЦТССт-2М, ЦТС-46 based on the lead titanate-zirconate solid solutions were used for fabrication of PCE. Model solid solution Pb(Zr₀.₅₂Ti ₀.₄₈)O₃ (PZT 52/48) doped with various chemical elements was used, too. The advantage of semiceramic method for ceramic elements fabrication has been shown. Обговорюються результати досліджень виробництва п'єзоелектричних керамічних елементів (ПКЕ) з високими значеннями п'єзочутливості g₃₃. Для виготовлення ПКЕ використано промислові матеріали ЦТССт-2М, ЦТС-46 на основі твердих розчинів титанату-цирконату свинцю. Використаний також модельний твердий розчин Pb(Zr₀.₅₂Ti ₀.₄₈)O₃, легований різними хімічними елементами. Показано перевагу напівкерамічного методу для виробництва керамічних елементів. Обсуждаются результаты исследований производства пьезоэлектрических керамических элементов (ПКЭ) с высокими значениями пьезочувствительности g₃₃. Для изготовления ПКЭ использованы промышленные материалы ЦТССт-2М, ЦТС-46 на основе твердых растворов титаната-цирконата свинца. Использован также модельный твердый раствор Pb(Zr₀.₅₂Ti ₀.₄₈)O₃ (ЦТС 52/48), легированный различными химическими элементами. Показано преимущество полукерамического метода для производства керамических элементов.